Potentially Inappropriate Medications Are Associated with Increased Healthcare Utilization and Costs. Issue 11 (5th August 2020) - Clark, Collin M.; Shaver, Amy L.; Aurelio, Leslie A.; Feuerstein, Steven; Wahler, Robert G.; Daly, Christopher J.; Jacobs, David M.
Abstract : BACKGROUND/OBJECTIVES: To examine the prevalence of potentially inappropriate medication (PIM) prescribing and its association with healthcare utilization and related expenditures utilizing nationally representative data from the United States. DESIGN: Retrospective cohort study. SETTING: The 2011–2015 Medical Expenditure Panel Survey (MEPS). PARTICIPANTS: Community‐dwelling sample of U.S. adults aged 65 and older during the first round of each MEPS cycle. MEASUREMENTS: A qualified definition operationalized from the 2019 American Geriatrics Society Beers Criteria® was used to estimate the prevalence of PIM prescribing over the study period. Negative binomial models were assembled to examine associations between PIM exposure and healthcare utilization including hospitalizations, emergency department (ED) visits, and outpatient provider visits. Generalized linear models with the log link function and gamma distribution were used to analyze associations between PIM exposure and healthcare expenditures. Sensitivity analyses were conducted utilizing inverse probability treatment weighting using propensity scores for being prescribed a PIM. RESULTS: The period prevalence of PIM prescribing over the 5‐year sample was 34.4%. PIM prescribing was positively associated with hospitalizations (adjusted incidence rate ratio [aIRR] = 1.17; 95 confidence interval [CI] = 1.08–1.26; P < .001), ED visits (aIRR = 1.26; 95% CI = 1.17–1.35; P < .001), and outpatient provider visits (aIRR = 1.18; 95% CI = 1.14–1.21; P < .001). PIM exposure was associated with higher marginal costs within outpatient visits ($116; 95% CI = $105–$243; P < .001), prescription medications ($128; 95% CI = $72–$199; P < .001), and total healthcare expenditures ($458; 95% CI = $295–$664; P < .001). Similar results were found in our propensity score analyses. CONCLUSION: PIMs continue to be prescribed at a high rate among older adults in the United States. Our results suggest that receipt of PIMs is associated with higher rates of healthcare utilization and increased costs across the healthcare continuum. Further work is needed to implement evidence‐based deprescribing interventions that may in turn reduce unnecessary healthcare utilization.